Analisis Kinerja Perbankan Syariah di Indonesia : Studi Masa Pandemi Covid-19 - Allselia Riski Azhari; Rofiul Wahyudi (JESI (Jurnal Ekonomi Syariah Indonesia), 2020)
The Covid-19 pandemic has spread to various countries, including Indonesia. As a result, almost all sectors experienced contractions, including Islamic banking. However, Islamic banking is considered quite capable of surviving the storm of impact based on the previous crises' empirical facts. The purpose of this study is to analyze how the performance of Islamic banking during the Covid-19 pandemic. This research method uses a descriptive approach with a sample of 14 Islamic Commercial Banks in Indonesia. Secondary data in the form of financial report panel data is the source of data for the January - July 2020 period, obtained from the monthly reports of each Islamic bank. The results showed that Islamic banking performance based on debt financing fluctuated, while the performance based on equity financing experienced growth. The performance of third party funds has fluctuated.